2018
DOI: 10.4269/ajtmh.18-0001
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Delay among Pulmonary Tuberculosis Patients within the Pakistan National Tuberculosis Control Program

Abstract: Delay in diagnosis and treatment worsens the disease and clinical outcomes, which further enhances transmission of tuberculosis (TB) in the community. Therefore, this study aims to assess treatment delay and its associated factors among pulmonary TB patients in Pakistan. A cross-sectional study was conducted among 269 pulmonary TB patients in the district. Binary and multivariate logistic regressions were used to explore the factors associated with delay in TB treatment. Results reveal that most patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 27 publications
9
15
0
Order By: Relevance
“…TB-related stigma was independently associated with non-submission of sputum, consistent with findings from a study in India [22]. Several studies have reported high perception of TB-associated stigma [23][24][25][26][27], and specific actions are needed to counter this [28,29].…”
Section: Discussionsupporting
confidence: 79%
“…TB-related stigma was independently associated with non-submission of sputum, consistent with findings from a study in India [22]. Several studies have reported high perception of TB-associated stigma [23][24][25][26][27], and specific actions are needed to counter this [28,29].…”
Section: Discussionsupporting
confidence: 79%
“…Treatment delay leads to more serious illness; as a result, it increased infectivity within the community and increased transmission of TB [ 3 , 4 ]. Delay in initiation of treatment gratuitously prolongs the period of TB transmission within the community [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…2 Patients with LTFU (previously referred to as defaulted) often have poorer treatment outcomes, higher risk of relapse, and are more prone to developing drug resistance. 4 7 Improving treatment completion and reducing LTFU is a key step toward TB control in India.…”
Section: Introductionmentioning
confidence: 99%